Smart Wearables as Early Warning Systems for Sedentary-Induced Health Risks in Youth: A Scoping Review of Sport and Health Perspectives - Satria Eureka Nurseskasatmata (Universitas Negeri Surabaya, 2025)
Lack of physical activity and increasing sedentary lifestyles among adolescents and young adults pose significant health risks, including metabolic and cardiovascular disorders. Wearable biosensor technologies such as smartwatches and fitness trackers have the potential to serve as early warning systems for health risks associated with sedentary behavior. This scoping review aims to map the trends, effectiveness, and challenges of using wearables to promote physical activity and monitor vital signs in young populations. A literature search was conducted across six leading databases, yielding 1,901 articles, with 24 studies meeting the inclusion criteria. Findings were grouped into six main themes: (1) user compliance and psychological factors, (2) impact on physical activity and sedentary behavior, (3) vital sign and biomarker monitoring, (4) sensor validity and reliability, (5) injury prevention and athlete performance enhancement, and (6) clinical implementation, ethics, and technology integration. Results show that wearables are capable of increasing physical activity, predicting health status through heart rate variability (HRV), and supporting decision-making in sports and clinics. However, long-term success is highly dependent on system integration, sensor validation, and sustainable real-world use. This study provides a scientific basis and strategic recommendations for the development of wearable-based health technology interventions in Indonesia